ANALISIS KEBUTUHAN PELATIHAN DEPARTEMEN QUALITY ASSURANCE DAN DEPARTEMEN ENGINEERING PT MILKO BEVERAGE INDUSTRY, BOGOR - Ajrina, Ajrina; Yuningsih, Erni (Fakultas Ekonomi Universitas Djuanda, 2016)
The research is conducted at PT. Milko Beverage Industry, Bogor. The purpose of the research is to know about : 1) how is the implementation of employee training, 2) how are the knowledge, skills and attitudes that employee have seen from KKJ and CTF and 3) how are the needs and training decisions based on the KKJ and CTF analysis. It uses Tool Training Need Assessment (TNA-T) method. The results show that the implementation of the training includes three stages; they are planning, implementation, and evaluation stage. The quality of knowledge, skills, and attitudes of the employees are quite good. The quality of knowledge and the skills of employes are quite good and the level attitude is a good interpretation. From the results of the analysis about the needs and priorities employees training decisions in areas B, is mean that it needs a training. The substances of the training include : subject of analysis capabilities, task management, and self-management for the QA department. While the Department of Engineering priorities are self-management, task management and capabilities.Keywords: Training Needs Analysis, KKJ and CTF